Detecção de oportunidades de refatoração em bases de dados relacionais - Fogliato Junior, Luiz (2015)
Many information systems that work with RDR (Relational Databases) have problems in the design of their databases. Such failures may result from design specification, requirement changes or even lack of knowledge to produce schemes that provide more evolutionary treatments for such systems. The technique that includes making changes to correct imperfections in databases that generate the mentioned problem is known as database refactoring. In order to identify possible opportunities for refactoring databases, this work proposes heuristics that detect or assist in detecting opportunities for refactoring. Thus, domain analysts and data professionals can identify the structure and data bad smells of a scheme and also take the necessary steps to address these shortcomings.